1984
DOI: 10.1038/bjc.1984.161
|View full text |Cite
|
Sign up to set email alerts
|

Second look laparotomy in the management of epithelial cell carcinoma of the ovary

Abstract: Summary Case histories from 20 patients undergoing postchemotherapy "second look" laparotomy for metastatic epithelial cell carcinoma of the ovary were reviewed in an attempt to evaluate the usefulness of this procedure and its likely impact on patient survival. The patient population comprised 18 patients treated with a combination of cisplatin, adriamycin and cyclophosphamide (PACe) and 2 patients treated with chlorambucil. The findings at second look were often predictable, and related to the adequacy of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The differences are, however, not statistically significant. These results are in agreement with recent studies (Mead et al 1984;Cain et al 1986;Podratz er al. 1985;Neijt et al 1984), which also have shown a relation between the small-sized residual tumour at primary surgery and the rate of complete pathological response.…”
Section: Discussionsupporting
confidence: 94%
“…The differences are, however, not statistically significant. These results are in agreement with recent studies (Mead et al 1984;Cain et al 1986;Podratz er al. 1985;Neijt et al 1984), which also have shown a relation between the small-sized residual tumour at primary surgery and the rate of complete pathological response.…”
Section: Discussionsupporting
confidence: 94%
“…Its role, as suggested by Mead et al (1984), should be solely in the setting up of a clinical trial to define the optimum, minimum chemotherapy or in the assessment of new, or new combinations of, chemotherapeutic agents. The mean duration of hospital stay was 7 days.…”
Section: Side-effectsmentioning
confidence: 99%
“…Apart from these patients second-look laparotomy can give valuable information in relation to prognosis, but unless a new generation of chemotherapeutic agents is devised it has little bearing on patient management or survival for patients who receive initial adequate clearance. Its role, as suggested by Mead et al (1984), should be solely in the setting up of a clinical trial to define the optimum, minimum chemotherapy or in the assessment of new, or new combinations of, chemotherapeutic agents.…”
Section: Side-effectsmentioning
confidence: 99%